THE INFLUENCE ANALYSIS OF PRICE AND PROMOTION ON THE DECISION TO PURCHASE PRODUCTS AT PT SHINTA POOLS AND WATERBOOM IN SOUTH JAKARTA - Wulansari, Retno; Faidah, Thalita Farah (International Journal of Multidisciplinary Research and Literature, 2024)
This study aimed to assess the simultaneous impact of price and promotion on product purchasing decisions at Shinta Pools & Waterboom South Jakarta. This study employs a quantitative research method. The sample employed is saturated, encompassing the entire population of 90 individuals. The data analysis methods used in this study are validity test, reliability test, normality test, multicollinearity test, heteroscedasticity test, simple linear regression test, multiple linear regression test, determination test and significance test. The results of the multiple linear regression equation Y = 4.769 + 0.643X1 + 0.703X2. The study's results obtained partial results that price significantly affects purchasing decisions; this can be seen from the t-test with a t count value of 6.449> t table 1.662 with a significance value of 0.001. This value is smaller than 0.1 (0.001 <0.1). Partially, the promotion has a significant effect on purchasing decisions; this can be seen from the t-test with a t count value of 6.010> t table 1.660 with a significance level of 0.001; this value is smaller than 0.1 (0.001 <0.1) and simultaneously price and promotion have a significant effect on purchasing decisions, this can be seen from the results of the F test with F count 123.850> F table 3.10 (123.850> 3.10). The coefficient of determination for Price (X1) and Promotion (X2) affecting Purchasing Decisions (Y) of swimming pools at Shinta Pools & Waterboom in South Jakarta is 74%, with the remaining 26% attributed to other variables. Consequently, it can be inferred that price and promotion concurrently exert a substantial influence on purchasing decisions